The Mortality from External Causes: Impact of the COVID-19 Pandemic and the War in Ukraine - Ryngach, N. О. (Statistics of Ukraine, 2023)
Extreme events (the COVID-19 pandemic and the Russian aggression beginning with 24.02.2022) had adverse effects for the number of premature deaths, the overall mortality, the death rate and structure due to external causes (ECs). While the change determined by spread of COVID-19 in 2019–2021 can be revealed with a high reliability by use of official statistics data, mortality statistics in Ukraine became hardly accessible after 24.02.2022. The exact number of deaths caused by the war (for military men and civil population alike) has not been known by now. Even on the territories outside the warfare zone, not all the death occurrences due to ECs have been identified and classified with accuracy. There exist a series of factors for the increased probability of death caused by ECs in time of war due to injuries provoked by warfare and other factors. The research objective is to assess the change in mortality due to external causes resulting from the spread of COVID-19 pandemic and the subsequent large-scale Russian invasion of Ukraine; to identify and assess risk factors with impact on this change, and, given the lack of updated statistical data, to articulate hypotheses on a probable change in the mortality by cause, on conformity with Chapter XX “External causes of morbidity and mortality” of the International Statistical Classification of Deceases and Related Health Problems (10th revision). An assessment of the prewar situation and the change in time of the COVID-19 pandemic was made by data of the State Statistics Service of Ukraine on the distribution of deaths by cause, gender and age for 2019–2021; the situation in time of the war was assessed by selected data of the official departmental statistics and data of international agencies for 2022. It was revealed that in 2021 a smaller share of deaths (3.20% against 4.25% in2019) fell into Chapter XX. Ukraine did not feature a reduced mortality due to ECs relative to 2019, with the estimate by Eurostandard being virtually unchanged. Factors determining the potentially increasing mortality due to ECs in Ukraine are as follows: the war and massive injuries (of military men and civil population) resulting from the warfare throughout the active period of war and its consequences, e. g. hitting by explosive devices after its cessation; the acute or chronic mental pressure with the majority of the population and the spreading post-traumatic disorders provoking the increasing scales of risky behaviors and suicide; ruining of transport infrastructures and loosening control over the traffic safety, especially in times of blackout; the increasing probability of unintentional poisoning (with chemical substances, carbon monoxide, poisonous plants and mushrooms, alcohol), thermal injuries and overcooling/frostbites. carbon monoxide The increasing mortality due to ECs (mainly from injuries resulting from warfare, suicides, injuries with undefined intentions, road traffic accidents or poisonings) was predicted for 2022–2023, for the period before the end of the war and in the short run after it, with the widening gap between the mortality of men and women. The additional factor increasing a probability of death from nonfatal injuries and traumas or preventable ECs is the worse access to the medical aid due to objective and/or subjective reasons and the overburdened health protection system.